Primary Intracranial Leiomyosarcoma Secondary to Glioblastoma: Case Report and Literature Review - Zhao, Liyan (Front Oncol, 2021)
BACKGROUND: Leiomyosarcoma is a highly malignant soft-tissue sarcoma with a poor prognosis. In recent years, treatment for leiomyosarcoma has not shown much progress. Primary intracranial leiomyosarcoma (PILMS) is a much rarer type of neoplasm, which occurs more frequently in immunocompromised patients. PILMS cases reported in the literature are scarce and treatment strategy and prognosis are still under debate. In this study, a case of PILMS secondary to the total resection of giant cell glioblastoma is reported. CASE DESCRIPTION: A 38-year-old male was hospitalized with a three-month history of a temporal opisthotic bump. His medical history included a total resection of a tumor located in the right temporal lobe performed 4 years earlier. Pathological examination led to a diagnosis of giant cell glioblastoma, and the patient underwent postoperative chemotherapy with temozolomide for 6 weeks plus simultaneous radiotherapy with 63.66 Gary. Four years later, during regular follow-up, a preoperative MRI brain scan resulted in a well-defined signal pointing out two nodule-like features located at the right temporal lobe and subcutaneous soft tissue, respectively, and near the area where the previous giant cell glioblastoma was located. The mass was completely removed by a transtemporal approach and postoperative pathology revealed that the mass was a leiomyosarcoma. The patient underwent postoperative radiotherapy and no recurrence occurred until now. CONCLUSIONS: To date, research on soft-tissue sarcoma, especially PILMS, has not made much progress, and a limited number of studies have provided few details on the management of PILMS. The treatment of choice for PILMS is aggressive multimodal treatment based on total tumor resection and radiotherapy. Moreover, systemic treatment with chemotherapy and targeted therapy, such as olaratumab, as well as further research still needs to be performed as many questions are left unanswered. To our knowledge, this is the first report on a case of PILMS secondary to glioblastoma, which might serve as a potential reference for clinicians and clinical studies.